Does Intellectual Capital and Islamic Corporate Governance Affect Financial Performance and Earning Management on Sharia Banking in Indonesia? - Abdurrahman Hasan; Amilin Amilin; Indo Yama Nasaruddin (AFEBI Islamic Finance and Economic Review, 2021)
This study aims to analyze the relationship between intellectual capital and Islamic corporate governance on financial performance and its impact on earning management behavior. This study uses the analysis method Generalize Least Square and Path Analysis in Islamic banking. The sampling technique used purposive sampling. The data obtained is secondary data based on financial reports for a period of 9 years in the period 2011-2019. The results showed that the role of intellectual capital and Islamic corporate governance can directly affect financial performance, and the role of intellectual capital and Islamic corporate governance cannot directly affect Earnings Management however must go through Financial Performance.